HB-EGF Plays a Pivotal Role in Mucosal Hyperplasia During Otitis Media Induced by a Viral Analog - Sakamoto, Takashi; Pak, Kwang; Chavez, Eduardo; Ryan, Allen F.; Kurabi, Arwa (Frontiers in Cellular and Infection Microbiology, 2022)
Otitis media (OM), the most common childhood illness, can be caused by bacterial and/or viral infection. Hyperplasia of the middle ear (ME) mucosa is an important component of OM that contributes to its deleterious sequelae. Our previous research revealed that ME mucosal hyperplasia in bacterially induced OM was associated with expression of the heparin-binding epidermal growth factor (HB-EGF) gene, and that HB-EGF induced the proliferation of ME mucosal explants in culture. We used single-cell RNA-Seq to identify ME cells that express Hbegf and related genes involved in mediating responses to this factor. To determine the degree to which a viral infection might induce mucosal hyperplasia, and to assess the role of HB-EGF in hyperplasia in vivo, we used, Poly(I:C) to simulate a ME viral infection, Western blotting to confirm ME protein expression, and a specific inhibitor to block the effects of HB-EGF during OM. Genes for HB-EGF and its receptor were expressed in the ME primarily by epithelial, stromal and endothelial cells. Poly(I:C) induced prominent ME mucosal hyperplasia, peaking two days after ME injection. Immunostaining revealed that cleavage of proHB-EGF into its soluble form (sHB-EGF) was strongly induced in response to Poly(I:C). Inhibition of the sHB-EGF receptor dramatically reduced the hyperplastic response of the mucosa. The results demonstrate that a synthetic analog of viral double-stranded RNA interaction can induce OM including a strong proliferative response of the ME mucosa, independent of bacteria. They also indicate that HB-EGF is the dominant growth factor responsible for ME mucosal hyperplasia in vivo.